The new normal in IT how the global pandemic changed information technology forever - Smith, Gregory S. 1963- (John Wiley & Sons, Inc., 2022)
"Until 2020, the IT operational and strategic playbooks for various industries were pretty set and focused around deploying applications, knowledge management systems, technology infrastructure via a mix of cloud and on-premise installations, and security -- mostly centered around physical office buildings and data centers where most staff worked. As a result of the global Covid-19 pandemic that originated in early 2020, everything IT related has changed and will likely remain different forever. Companies are moving to full or partial remote workers with more tolerance for broader geographical ranges of resources. In addition, they are shedding corporate office locations or at a minimum, reducing the office footprint significantly to reduce costs. Why? Because the pandemic of 2020-2021 showed how valuable information technology can be to an organization and that organizations are more productive working remotely away from expensive corporate office buildings. The role of the CIO / CTO going forward will change globally forever as a result. The purpose of this book is to share the experiences of CIOs across a diverse set of sectors (energy, manufacturing, academia, transportation, consumer products, financial services, and non-profits) regarding the future strategy deployment of technology post Covid-19. Three broad areas will be covered: (1) what the post-pandemic new normal looks like for IT leaders regarding resource sourcing, the office of the future and how collaboration tools will continue to accelerate a hybrid office/remote work force across the globe; (2) how risk mitigation and specifically disaster recovery testing and planning will adapt to include worst case scenarios; and (3) CIOs/CTOs will share how today's CIOs are adapting their IT governance approach to meet the new IT normal and how key performance indicators will likely change as a result."--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on March 08, 2022)
Keywords: Data processing service centers; Information technology; COVID-19 Pandemic, 2020- -- Influence; COVID-19 Pandemic; (2020-); Since 2020; Centres de traitement de l'information; Technologie de l'information; computer centers; information technology; Influence (Literary, artistic, etc.)